Keystone Perforator Island Advancement Flap as Another Option for Closure after Radical Excision of Axillary Hidradenitis Suppurativa - Timea H. Virag; Geoffrey G. Hallock; Ileana R. Matei; Alexandru V. Georgescu (Archives of Plastic Surgery, 2025)
Surgical treatment of axillary hidradenitis suppurativa (HS) requires wide excision followed by definitive wound closure to not limit shoulder function. An international prospective study was undertaken to compare how a keystone perforator island advancement flap can be a reliable solution. Independently, two Transatlantic institutions, from 2019 to 2024, surgically resected axillary HS followed by a keystone perforator flap for defect management. A total of 23 patients were treated, including 4 with bilateral disease, employing 27 total flaps that permitted the comparison of demographic data, Hurley disease stage, flap viability and complications, need for secondary surgeries, duration of treatment, and functional outcome. Demographic data in both countries was similar with regard to mean age, female preponderance, presence of obesity, and prior means of treatment. Surgical treatment was not limited in either country only to Hurley stage III individuals. In Romania, 6/11 (54.5%) compared to 3/12 (25.0%) of U.S. patients were classified as Hurley stage II. No flap necrosis was observed, allowing unrestricted shoulder mobility within 3.5 (2–4) months in Romania, but more slowly by 4.4 (3–9) months in the United States. All complications were minor, occurring in 11 (43.5%) patients, albeit three times more frequently in the United States. Overall, the most common problem was lesser curvature dehiscence (63.6%). No disease recurrences were noted. The keystone perforator island advancement flap is a safe, rapid, and simple local flap option for the closure of the axillary defect after the excision of HS. The learning curve was straightforward, so reconstructive surgeons can readily adapt to utilize this approach.